Pencegahan Perundungan/Bullying di Insititusi Pendidikan: Pendekatan Norma Hukum dan Perubahan Perilaku - Rika Saraswati; Venatius Hadiyono (Jurnal Hukum, Politik dan Kekuasaan, 2020)
Bullying is one kind of violence against students at school in Indonesia. The violence has recently been reported among adolescents at Junior and Senior High School level in Semarang city. The responsibility of the Indonesian government in preventing bullying at school has been carried out through a national level by issuing the Child Protection Act  in 2002 (was amended in 2014) and the Ministry of Education and Culture Regulation No. 82 of 2015 in order to support zero tolerance in school. However, there is a lack implementation of the legislation. It seems that the legal norm approach must be accompanied by behavioral changes from the students, the teachers and the community members.  This study used a qualitative approach to determine the factors that cause bullying at school and the prevention efforts. Data obtained through literature and empirical studies related to bullying experiences of students in junior and senior high school in Semarang city. The research demonstrates that the effort to prevent bullying at school by targeting certain students to spread anti-bullying messages is more effective to change students’ behaviour than merely using the legal norm approach.